Graphene quantum dots: wave function mapping by scanning tunneling spectroscopy and transport spectroscopy of quantum dots prepared by local anodic oxidation - Morgenstern, Markus; Freitag, Nils; Vaid, Aviral; Pratzer, Marco; Liebmann, Marcus (Physica Status Solidi-Rapid Research Letters, 2016)
3D view of STM image of graphene supported by SiO2 [1, 2]; Insets (from left to right): STM image of graphene nanoislands on Ir(111) and scanning tunneling spectroscopy images of the three low energy wave functions of a particular nano-island [3]. (C) 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhe
Keywords: graphene; quantum dots; edge states; scanning tunneling microscopy; local anodic oxidation; metallic substrates